Funcionamiento familiar y autoconcepto de los alumnos del sexto grado de las instituciones educativas de la Red 8 Callao - Chuquillanqui Portocarrero, Irma Solange (2012)
The present investigation studied the relationship between family functioning and selfconcept of the sixth grade primary students of Network 8 Callao. The sample was made of 274 students selected at random. We used the scale of Adaptation and Family Cohesion III to evaluate family functioning, and the self-concept questionnaire to evaluate self-concept. We used frequency distribution for the descriptive analysis and Chi² for the inferential analysis. The variable Family Functioning was evaluated in its two dimensions: cohesion and adaptability associating the levels of both dimensions with the levels of self-concept dimensions. The results show that there is a relation between cohesion dimension and self-concept: familiar, social acceptance, self evaluation and self control. They also show that there is no relation regarding physical self-concept. The adaptability dimension there was not related to any dimensions.